The perfect storm: A case of COVID-19 infection in an adolescent patient with EVALI. (2020) - Bozkanat, Kubra Melike; Rao, Devika R.; Lieu, Tiffany J.; Rivera-Sanchez, Yadira M.
Abstract: COVID-19 and EVALI share imaging findings and clinical features, including fever, respiratory, and gastrointestinal symptoms. To our knowledge, the clinical picture in patients presenting with both conditions simultaneously has not been reported. We present the case of a 17-year-old male with COVID-19 and EVALI, his hospital course, and clinical outcome.